Learning Salesforce Visual Workflow and Process Builder - Second Edition. - Gupta, Rakesh (Packt Publishing, 2017)
Click your way to automating various business processes using Salesforce Visual WorkflowAbout This Book* Develop an application using Point and Click with the help of Flow* Get to grips with various ways to launch a Flow* Capture data from an external user without using the Visualforce page* Save user input into the database, and learn how to query and manipulate the data* Discover various ways to debug and deploy Flow and Process Builder* Understand the concepts of Subflow and Login Flow* Handle complex business processes using Process builder and keep them clean* Use existing or new Flows to work with Salesforce Lightning Experience. Who This Book Is ForThis book is intended for those who want to use Flows to automate their business requirements by clicking, not coding. No previous experience in computer coding or programming is required. What You Will Learn* Develop an application using point and click with the help of Flow* Get to grips with various ways to launch a Flow* Capture data from an external user without using the Visualforce page* Save user input into the database, and learn how to query and manipulate the data* Discover various ways to debug and deploy Flow and Process Builder* Understand the concepts of Subflow and Login Flow* Handle complex business processes using Process builder and keep them clean* Use existing or new Flows to work with Salesforce Lightning Experience. In DetailSalesforce Management System is an information system used in CRM to automate the business processes like sales and marketing. To implement this, Force.com developed a powerful tool called Visual Workflow to automate business processes by creating applications also called Flows. Learning Salesforce Visual Workflow, Second Edition is a practical guide on Flows that will enable you to develop custom applications in Salesforce with minimized code usage. The book starts with an introduction to Visual Workflows that teaches all the building blocks of creating Flows and use it efficiently. You will learn how to easily automate business processes and tackle complex business scenarios using Flows. The book explains the working of the Process Builder so you can create reusable processes. The book also covers how you can integrate existing or newly created Flows with the Salesforce Lightening Experience. By the end of the book, you will get a clear understanding on how to use Flows and Process Builder in your organization to optimize code usage. Style and approachStep by step approch to use Process Builder to solve complex business requirements with the help of Flow.